Quantitative magnetic resonance neurography in chronic inflammatory demyelinating polyradiculoneuropathy: a longitudinal study over 6 years - Preisner, Fabian; Pitarokoili, Kalliopi; Lueling, Benjamin; Motte, Jeremias; Fisse, Anna Lena; Grueter, Thomas; Godel, Tim; Schwarz, Daniel; Heiland, Sabine; Gold, Ralf; Bendszus, Martin; Kronlage, Moritz (Annals of Clinical and Translational Neurology, 2023)
ObjectiveTo evaluate magnetic resonance neurography (MRN) for the longitudinal assessment of patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). MethodsProspective examination of twelve CIDP patients by neurological assessment, MRN, and nerve conduction studies in 2016 and 6 years later in 2022. Imaging parameters were compared with matched healthy controls and correlated with clinical and electrophysiological markers. The MRN protocol included T2-weighted imaging, diffusion tensor imaging (DTI), T2 relaxometry, and magnetization transfer imaging (MTI). ResultsNerve cross-sectional area (CSA) was increased in CIDP patients compared to controls (plexus: p = 0.003; sciatic nerve: p < 0.001). Over 6 years, nerve CSA decreased in CIDP patients, most pronounced at the lumbosacral plexus (p = 0.015). Longitudinally, changes in CSA correlated with changes in the inflammatory neuropathy cause and treatment validated overall disability sum score (INCAT/ODSS) (p = 0.006). High initial nerve CSA was inversely correlated with changes in the INCAT/ODSS over 6 years (p < 0.05). The DTI parameter fractional anisotropy (FA) showed robust correlations with electrodiagnostic testing both cross-sectionally and longitudinally (p < 0.05). MTI as a newly added imaging technique revealed a significantly reduced magnetization transfer ratio (MTR) in CIDP patients (p < 0.01), suggesting underlying changes in macromolecular tissue composition, and correlated significantly with electrophysiological parameters of demyelination (p < 0.05). InterpretationThis study provides evidence that changes in nerve CSA and FA reflect the clinical and electrophysiological course of CIDP patients. Initial nerve hypertrophy might predict a rather benign course or better therapy response.